"Ask for More Time": Big Data Chronopolitics in the Australian Welfare Bureaucracy. (September 2020) - Whelan, Andrew
Since 2016, welfare recipients in Australia have been subject to the Online Compliance Intervention (OCI), implemented through the national income support agency, Centrelink. This is a big data initiative, matching reported income to tax records to recoup welfare overpayments. The OCI proved controversial, notably for a "reverse onus, " requiring that claimants disprove debts, and for data-matching design leading frequently to incorrect debts. As algorithmic governance, the OCI directs attention to the chronopolitics of contemporary welfare bureaucracies. It outsources labor previously conducted by Centrelink to clients, compelling them to submit documentation lest debts be raised against them. It imposes an active wait against a deadline on those issued debt notifications. Belying government rhetoric about the accessibility of the digital state, the OCI demonstrates how automation exacerbates punitive welfare agendas, through transfers of time, money, and labor whose combined effects are such as to occupy the time of people experiencing poverty.